Correction of hysteretic respiratory motion in SPECT myocardial perfusion imaging: Simulation and patient studies. Issue 2 (16th February 2017) - Dasari, Paul K. R.; Könik, Arda; Pretorius, P. Hendrik; Johnson, Karen L.; Segars, William P.; Shazeeb, Mohammed S.; King, Michael A.
Abstract : Purpose: Amplitude‐based respiratory gating is known to capture the extent of respiratory motion (RM) accurately but results in residual motion in the presence of respiratory hysteresis. In our previous study, we proposed and developed a novel approach to account for respiratory hysteresis by applying the Bouc–Wen (BW) model of hysteresis to external surrogate signals of anterior/posterior motion of the abdomen and chest with respiration. In this work, using simulated and clinical SPECT myocardial perfusion imaging (MPI) studies, we investigate the effects of respiratory hysteresis and evaluate the benefit of correcting it using the proposed BW model in comparison with the abdomen signal typically employed clinically. Methods: The MRI navigator data acquired in free‐breathing human volunteers were used in the specially modified 4D NCAT phantoms to allow simulating three types of respiratory patterns: monotonic, mild hysteresis, and strong hysteresis with normal myocardial uptake, and perfusion defects in the anterior, lateral, inferior, and septal locations of the mid‐ventricular wall. Clinical scans were performed using a Tc‐99m sestamibi MPI protocol while recording respiratory signals from thoracic and abdomen regions using a visual tracking system (VTS). The performance of the correction using the respiratory signals was assessed through polar map analysis in phantom and 10 clinical studies selected on the basis of having substantial RM. Results: In phantom studies, simulations illustrating normal myocardial uptake showed significant differences ( P < 0.001) in the uniformity of the polar maps between the RM uncorrected and corrected. No significant differences were seen in the polar map uniformity across the RM corrections. Studies simulating perfusion defects showed significantly decreased errors ( P < 0.001) in defect severity and extent for the RM corrected compared to the uncorrected. Only for the strong hysteretic pattern, there was a significant difference ( P < 0.001) among the RM corrections. The errors in defect severity and extent for the RM correction using abdomen signal were significantly higher compared to that of the BW (severity = −4.0%, P < 0.001; extent = −65.4%, P < 0.01) and chest (severity = −4.1%, P < 0.001; extent = −52.5%, P < 0.01) signals. In clinical studies, the quantitative analysis of the polar maps demonstrated qualitative and quantitative but not statistically significant differences ( P = 0.73) between the correction methods that used the BW signal and the abdominal signal. Conclusions: This study shows that hysteresis in respiration affects the extent of residual motion left in the RM‐binned data, which can impact wall uniformity and the visualization of defects. Thus, there appears to be the potential for improved accuracy in reconstruction in the presence of hysteretic RM with the BW model method providing a possible step in the direction of improvement.